Clinical Potential of Hypoxia Inducible Factors Prolyl Hydroxylase Inhibitors in Treating Nonanemic Diseases - Miao, Mengqiu; Wu, Mengqiu; Li, Yuting; Zhang, Lingge; Jin, Qianqian; Fan, Jiaojiao; Xu, Xinyue; Gu, Ran; Hao, Haiping; Zhang, Aihua; Jia, Zhanjun (Frontiers in Pharmacology, 2022)
Hypoxia inducible factors (HIFs) and their regulatory hydroxylases the prolyl hydroxylase domain enzymes (PHDs) are the key mediators of the cellular response to hypoxia. HIFs are normally hydroxylated by PHDs and degraded, while under hypoxia, PHDs are suppressed, allowing HIF-α to accumulate and transactivate multiple target genes, including erythropoiesis, and genes participate in angiogenesis, iron metabolism, glycolysis, glucose transport, cell proliferation, survival, and so on. Aiming at stimulating HIFs, a group of small molecules antagonizing HIF-PHDs have been developed. Of these HIF-PHDs inhibitors (HIF-PHIs), roxadustat (FG-4592), daprodustat (GSK-1278863), vadadustat (AKB-6548), molidustat (BAY 85-3934) and enarodustat (JTZ-951) are approved for clinical usage or have progressed into clinical trials for chronic kidney disease (CKD) anemia treatment, based on their activation effect on erythropoiesis and iron metabolism. Since HIFs are involved in many physiological and pathological conditions, efforts have been made to extend the potential usage of HIF-PHIs beyond anemia. This paper reviewed the progress of preclinical and clinical research on clinically available HIF-PHIs in pathological conditions other than CKD anemia.